2021
DOI: 10.3389/fphar.2021.732496
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D Supplementation on Anthropometric and Biochemical Indices in Patients With Non-alcoholic Fatty Liver Disease: A Systematic Review and Meta-analysis

Abstract: Background: Vitamin D was reported to be associated with non−alcoholic fatty liver disease (NAFLD). This systematic review and meta−analysis aimed to investigate the effects of the vitamin D supplementation on anthropometric and biochemical indices in patient with NAFLD.Methods: PubMed, Web of science, Scopus, and Embase databases were explored to identify all randomized controlled trial (RCT) investigating the effects of vitamin D supplementation on anthropometric and biochemical indices in patients with NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…The duration of vitamin D supplementation ranged from 8 to 43 weeks. The location of the studies were as follows: four in China ( 20 , 24 26 ), two in Iran ( 18 , 27 ), two in United States ( 28 , 29 ), one each in Philippines ( 30 ), Bahrain ( 17 ), India ( 19 ), Australia ( 31 ), United Kingdom ( 32 ), and Brazil ( 33 ). Table 1 describes the quality of randomized controlled trials that were included in the included meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of vitamin D supplementation ranged from 8 to 43 weeks. The location of the studies were as follows: four in China ( 20 , 24 26 ), two in Iran ( 18 , 27 ), two in United States ( 28 , 29 ), one each in Philippines ( 30 ), Bahrain ( 17 ), India ( 19 ), Australia ( 31 ), United Kingdom ( 32 ), and Brazil ( 33 ). Table 1 describes the quality of randomized controlled trials that were included in the included meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the meta-analysis are also contradictory in this regard. While some meta-analysis studies show a positive effect of the vitamin D supplement on weight loss and waist circumference ( 17 , 18 ), some have reported ineffectiveness of the supplementation on anthropometric indices ( 19 , 20 ). Therefore, we conducted present umbrella meta-analysis to clarify the effect of vitamin D supplementation on anthropometric indices in different health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the efficacy of 6 months of intramuscular vitamin D supplementation in improving liver-related parameters in NAFLD patients found that a single monthly intramuscular dose of cholecalciferol was effective in improving laboratory and fibroscan markers in NAFLD patients [ 128 ]. The effect of vitamin D supplementation on anthropometric and biochemical variables in NAFLD patients was investigated in a recent meta-analysis; the results showed that vitamin D significantly improved indices such as high-density lipoprotein-cholesterol, body weight, body mass index, waist circumference, serum alanine transaminase, serum fasting blood glucose, homeostatic model assessment for insulin resistance (HOMA-IR), and calcium markers, suggesting its use as an alternative treatment strategy for NAFLD patients [ 129 ].…”
Section: Possible Mechanisms Of the Association Between Vitamin D–vdr...mentioning
confidence: 99%
“…Recently, extra-hepatic health benefits were reported following vitamin D supplementation in NAFD [improvements in HDL-cholesterol, body weight, BMI, ALT, insulin resistance and fasting glycaemia], the authors suggesting that vitamin D supplementation should be included in the management of patients with NAFDL. [51]. Covid-19 illness.…”
Section: Than Any Others Remains Unacceptable Since Deficiency Increa...mentioning
confidence: 99%